2023
DOI: 10.1186/s12884-023-05438-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ratios of estradiol increase on the outcome of in vitro fertilization-embryo transfer with antagonist regimens: a single center retrospective cohort study

Abstract: Background The outcome of in vitro fertilization-embryo transfer (IVF) is often determined according to follicle and estradiol levels following gonadotropin stimulation. In previous studies, although most of them analyzed the estrogen level from ovaries or the average estrogen level of a single follicle, there was no study on the ratio of estrogen increase, which was also correlated with pregnancy outcomes in the clinic. This study aimed to make timely adjustments to follow-up medication to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Many research in hints that successful IVF and a healthy pregnancy is associated with the levels of estrogen. Currently, a number of studies suggested that levels of hormones such as E 2 may play a role in predicting successful pregnancy in IVF cycles [5,6], but these results are controversial [7,8]. What's more, most previous studies paid attention to the association of clinical outcomes with E 2 on the day of β-hCG administration, or E 2 related with fresh embryo transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Many research in hints that successful IVF and a healthy pregnancy is associated with the levels of estrogen. Currently, a number of studies suggested that levels of hormones such as E 2 may play a role in predicting successful pregnancy in IVF cycles [5,6], but these results are controversial [7,8]. What's more, most previous studies paid attention to the association of clinical outcomes with E 2 on the day of β-hCG administration, or E 2 related with fresh embryo transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches in hints that successful IVF and a healthy pregnancy is associated with the levels of estrogen. Currently, a number of studies suggested that levels of hormones such as E 2 may play a role in predicting successful pregnancy in IVF cycles [ 3 , 4 ], but some results are controversial [ 5 , 6 ]. What’s more, most previous studies paid attention to the association of clinical outcomes with E 2 on the day of β-hCG administration, or E 2 related with fresh embryo transplantation.…”
Section: Introductionmentioning
confidence: 99%